A rare case of Monteggia fracture dislocation with distal radius epiphyseal injury in a 12-year-old male: case report and review of literature - Kumar, Sachin; Mane, Akash N.; Thakur, Rajesh (International Journal of Research in Orthopaedics, 2025)
Monteggia fracture dislocation is a fracture of proximal ulna with dislocation of radial head. Its association with ipsilateral distal radius fracture is very rare and only ten cases have been reported in the English literature. Authors report a case of a 12 years old male, who sustained Monteggia fracture with ipsilateral distal radius epiphyseal injury following a fall while playing cricket. He was managed conservatively at a local centre elsewhere. As the fracture was found to be displaced, surgical fixation was done at our hospital. At 3 months follow up, the fracture was found to have united and the child had a good functional range of motion. Early diagnosis and one stage surgical management can lead to a satisfactory outcome even in these complex fracture dislocations.